DEVELOPMENT AND VALIDATION OF STABILITY INDICATING REVERSE PHASE HIGH‑PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR SIMULTANEOUS ESTIMATION OF ATENOLOL, HYDROCHLOROTHIAZIDE AND LOSARTAN IN BULK AND PHARMACEUTICAL DOSAGE FORM - Neelima, Meesala Santhi; GANDHI, BONTHU MOHAN; Raju, Vatchavai Bhaskara; Sumanth, Kamatham Srinivas; Srinivas, Kolli; Mounika, Pasala; Lakshmi, Pedaprolu Jhansi Naga (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of present work was to develop and validate a simple, fast, precise, selective and accurate reverse phase high-performance liquid chromatography method for the simultaneous determination atenolol (ATN), hydrochlorothiazide (HCTZ) and losartan (LOS) in a pharmaceutical dosage form. Methods: The separation of these three drugs was achieved on an SHISHEDO C , 250 mm × 4.6 mm, 5 µ size column with a mobile phase consisting of acetonitrile and 0.5% orthophosphoric acid (30:70 v/v) at a flow rate of 1 ml/minute and UV detection at 224 nm. 18 Results: The retention times were observed to be 2.242, 3.963 and 6.733 minutes for ATN, HCTZ and LOS, respectively. Linearity was found to be 4-12 μg/ml, 4-12 μg/ml, 1-3 μg/ml for ATN, HCTZ and LOS, respectively. The method was statistically validated for linearity, recovery, the limit of detection (LOD), limit of quantification (LOQ), accuracy and precision. The stress testing of the drugs individually and their mixture is carried out under acidic, alkaline, oxidation, photo-stability and thermal degradation conditions and its degradation products is well-resolved from the analyte peaks. Conclusion: This method was successfully validated for accuracy, precision, and linearity, LOD and LOQ. Keywords: Atenolol, Hydrochlorothiazide, Losartan, Reverse phase high-performance liquid chromatography.